Radio Quotient Square Sum Labeling of a Graph - Raveendran, Swapna; Selvarajan, T.M. (International Journal of Psychosocial Rehabilitation, 2020)
A radio quotient square sum labeling is a one to one mapping p from V (G) to N satisfying the condition d (u, v) + ⌈ [